Pemberdayaan Griyo Maos Banyu Ilmu untuk Meningkatkan Softskill dan Hardskill Anak Dusun Rembukidul, Mojokerto - Rizka Nur Oktaviani; Wulan Trisnawaty; Indaria Tri Hariyani (Universitas Mathla'ul Anwar Banten, 2020)
EMPOWERMENT OF GRIYO MAOS BANYU ILMU TO IMPROVE CHILDREN'S SOFT SKILLS AND HARD SKILLS IN REMBUKIDUL VILLAGE, MOJOKERTO. The aims of this community service was improving softskills and hardskills of children in Rembukidul village. This research was Mixed Research by adopting of Kemmis and Mc Taggart models. Subjects in this study were 25 children in RembuKidul village. The partner in this community service was Griyo Maos Banyu Ilmu at Rembukidul village, Mojokerto. The data was analyze descriptively quantitative by calculating gainscore. From the results of this observations it can be concluded that the softskills development activities of children in Rembukidul village in coloring and finger painting activities amounted to 80.7 with excellent categories, storytelling and determining the story elements of 79.5 in the good category, composing panthaps for 71.6 in the good category , and recited poetry of 82.9 in the excellent category. While hardskill children in Rembukidul village increase in four activities included recognizing numbers which increased by 0.61 in the medium category, playing using abacus increased by 0.71 with a high category, arithmetic operations increased by 0.68 with the medium category, and counting using abacus with an increase of 0.65 in the medium category. So it can be concluded in that the empowerment of Griyo Maos Banyu Ilmu can be increasing the softskills and hardskills of children in Rembukidul village.